An Analysis of Defense Mechanisms in the Album Vessel (2013) by Twenty One Pilots - Muhammad Fadhil Ridwan; Nia Nafisah (Passage: Journal of English Language and Literature, 2024)
Mental health disorders have led to an increase and cause of personality problems and suicidal thoughts. Music, as an art form, often serves as a medium through which artists release their negative thoughts, emotions and experiences. In song lyrics, we can see the manifestation of defense mechanisms used by the speaker. As Cramer (2000) states, a defense mechanism is an attempt as a psychological strategy to reduce or avoid adverse circumstances such as conflict, frustration, anxiety, and stress. This study aims to identify what types of defense mechanisms are used by the speaker contained in the lyrics of five Twenty One Pilots songs in the album Vessel (2013) titled “Ode To Sleep”, “Migraine”, “Car Radio”, “Guns for Hands” and “Holding On To You”. This research used a qualitative method with the theoretical framework of defense mechanisms by Freud (1936/2018) and Cramer (2015). It was found that several types and the level stages of defense mechanisms used by the speaker in the five songs of Twenty One Pilots album Vessel (2013) are as follows: Neurotic defenses: displacement (2), Immature defenses: projection (1), and Mature defenses: suppression (5), altruism (5), sublimation (1), and intellectualization (1). This research provides new insights to readers about the main theme of the album Vessel (2013) and the types of defense mechanisms used by the speaker from Twenty One Pilots. This research also confirms that music can be used as a medium to channel negative feelings and anxiety experienced by songwriters as their defense mechanism.